(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
Knot in a noose encircling the neck has its own forensic significance in cases of hanging. The pattern of ligature mark and the mechanism of death in hanging with different knot positions are found in literature. However, when such knots are absent in noose, the post-mortem findings are different, which needs to be discussed. We report one such case of hanging, where neck compression had occurred by a ligature material with a loop that did not encircle the neck and did not bear a knot. The findings are discussed along with the mechanism of death in such cases along with a review of literature.